The Effect of Leadership, Motivation, and Work Discipline on Employee Performance at PT. ABCD at Jakarta - Musyasaroh; Febrian, Wenny Desty (International Journal of Advanced Multidisciplinary, 2025)
This study aims to examine the influence of leadership, motivation, and work discipline on employee performance. The sample used was a saturated sample or population of 33 people where all employees working at PT. ABCD, North Jakarta, was used as a respondent. This study uses regression analysis with the help of IBM SPSS Statistics Version 26 as a tool used for data processing and analysis that has statistical analysis capabilities and a data management system with a graphing environment. The results of this study show that leadership has a positive and significant effect on performance with a percentage of 60.1% and a regression value of 0.479, motivation has a positive and significant effect on performance with a percentage of 59.5% and a regression value of 0.385, work discipline has a positive and significant effect on performance with a percentage of 67.2% and a regression value of 0.591. And the results of the f-test or simultaneous test showed that leadership, motivation and work discipline had a positive and significant effect simultaneously on performance with a Fcal value of 24.339 greater than Ftable 2.93 and a propriety value of 0.000 smaller than a significant value of 0.05.